A Nano-Structured SOFC Composite Cathode Prepared via Infiltration of La0.5Ba0.25Sr0.25Co0.8Fe0.2O3-δ into La0.9Sr0.1Ga0.8Mg0.2O3-δ for Extended Triple-Phase Boundary Area. Issue 12 (22nd July 2019) - Lee, Seungtae; Kim, Seona; Choi, Sihyuk; Shin, Jeeyoung; Kim, Guntae
Abstract : Mixed ionic and electronic conductors (MIECs) show greatly enhanced electrochemical properties as cathode materials for intermediate-temperature solid oxide fuel cells (IT-SOFCs). Among promising MIEC candidates, La0.5 Ba0.25 Sr0.25 Co0.8 Fe0.2 O3- δ (LBSCF) is chosen as a cathode material in this study due to its high oxygen ion diffusivity and oxygen reduction reaction (ORR) activity. It is well known that the composite configuration with superior oxygen ion conductor, e.g., La0.9 Sr0.1 Ga0.8 Mg0.2 O3- δ (LSGM), results in the improvement of cell performance. Here, we successfully fabricate the LBSCF-LSGM composite cathode by infiltration method at a low sintering temperature (< 800°C), and thus nanoparticles are uniformly distributed on the LSGM porous scaffold. A half-cell exhibits an extremely low area-specific resistances (ASRs) of 0.010, 0.020, and 0.049 Ω cm 2 at 700, 650, and 600°C, respectively. Further, the peak power density about 0.9 W cm −2 is attained at 700°C, suggesting that infiltrated LBSCF-LSGM composite demonstrates sufficient ORR activities at an intermediate temperature and thus to be a highly promising cathode material for IT-SOFCs.